Sacral neuromodulation for constipation and fecal incontinence in children and adolescents - study protocol of a prospective, randomized trial on the application of invasive vs. non-invasive technique - Besendörfer, Manuel; Kirchgatter, Annemarie; Carbon, Roman; Weiß, Christel; Müller, Hanna; Matzel, Klaus E.; Diez, Sonja (Trials, 2024)
Background: A therapeutic effect of sacral neuromodulation (SNM) on fecal incontinence (FI) and quality of life has been proven in adults. SNM is, however, rarely used in pediatric cases. The aim of the study is to investigate effects of SNM in pediatric constipation in a prospective parallel-group trial. Methods: A monocentric, randomized, unblinded, parallel-group trial is conducted. SNM is conducted in the invasive variant and in an innovative, external approach with adhesive electrodes (enteral neuromodulation, ENM). We include patients with constipation according to the ROME IV criteria and refractory to conventional options. Patients with functional constipation and Hirschsprung’s disease are able to participate. Participants are allocated in a 1:1 ratio to either SNM or ENM group. Clinical data and quality of life is evaluated in regular check-ups. Neuromodulation is applied continuously for 3 months (end point of the study) with follow-up-points at 6 and 12 months. Findings are analyzed statistically considering a 5% significance level (p ≤ 0.05). Outcome variables are defined as change in (1) episodes of abdominal pain, (2) episodes of FI, (3) defecation frequency, (4) stool consistency. Improvement of proprioception, influence on urinary incontinence, quality of life and safety of treatment are assessed as secondary outcome variables. We expect a relevant improvement in both study groups. Discussion: This is the first trial, evaluating effects of neuromodulation for constipation in children and adolescents and comparing effects of the invasive and non-invasive application (SNM vs. ENM). Trial registration: The study is registered with clinicaltrials.gov, Identifier NCT04713085 (date of registration 01/14/2021).